PENGARUH PREFERENSI PEMBAYARAN DIGITAL, KEMUDAHAN AKSES LAYANAN, WAKTU PELAPORAN, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN PEMBAYARAN PAJAK ORANG PRIBADI DI JAKARTA UTARA - Florencia, Chika; Iskandar, Deni (Jurnal Akuntansi, 2026)
Tax compliance remains an important issue in supporting state revenue, particularly among individual taxpayers in the digital era. The increasing use of digital systems in taxation requires taxpayers to adapt to new methods of payment and reporting. This study aims to analyze the effect of digital payment preferences, ease of service access, tax reporting time, and taxpayer awareness on individual taxpayer compliance. Quantitative research is the method implemented by this research with data collected from 150 respondents through questionnaires, followed by validity and reliability testing. The results indicate that tax payment compliance is positively and significantly effected by all variables, with ease of service access showing the strongest influence, followed by digital payment preferences, taxpayer awareness, and tax reporting time. These findings suggest that improving digital services, accessibility, and taxpayer awareness can enhance voluntary compliance. Thus, strengthening digital tax systems and increasing public awareness are essential to improving taxpayer compliance.